Analysis of the Relationship Between Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), and Red Blood Cell Distribution Width (RDW) With Colorectal Cancer Staging - Mei Vrayanti F.S; Jelita Siregar; Adi Muradi Muhar (Indonesian Journal of Global Health Research, 2026)
This study aimed to examine the relationship between the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) with colorectal cancer (CRC) staging. Colorectal cancer is one of the most prevalent malignancies worldwide and a leading cause of cancer-related mortality, particularly in Indonesia. Inflammation plays an important role in cancer progression, and systemic inflammatory markers such as NLR, PLR, and RDW are considered practical, accessible, and cost-effective indicators for assessing disease severity and prognosis. An observational analytic study with a cross-sectional design was conducted at H. Adam Malik General Hospital, Medan, from November 2024 to January 2025. A total of 56 newly diagnosed CRC patients who had not undergone surgery or chemotherapy were enrolled using consecutive sampling. Blood samples were analyzed using a Sysmex XN-1500 hematology analyzer. Statistical analyses included independent t tests, Mann–Whitney tests, Spearman correlation, and receiver operating characteristic (ROC) analysis. The results demonstrated a significant difference in PLR values between early- and advanced-stage CRC (p = 0.003), with a moderate positive correlation between PLR and cancer stage (r = 0.297, p = 0.026). RDW showed a weak but statistically significant correlation with CRC stage (r = 0.284, p = 0.034). In contrast, NLR did not show a statistically significant correlation with CRC staging (p = 0.109). These findings suggest that PLR and RDW are promising, simple, and inexpensive inflammatory biomarkers that may assist in the preoperative staging of colorectal cancer, whereas NLR alone may not be a reliable predictor of CRC stage.